High-efficiency high-temperature acid leaching treatment process for refining high-purity quartz sand
Through the high-temperature acid leaching treatment process, fluorine-containing waste sulfuric acid, reducing agent or chelating agent, the problems of limited effect and high cost of quartz sand are solved, and the high purity and high whiteness of quartz sand are achieved, which significantly improves the pickling efficiency and eliminates waste sulfuric acid.
Patent Information
- Application Number
- CN202411980302.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to effectively treat fluorine-containing waste sulfuric acid, and the quartz sand pickling process has problems such as limited effect and high cost, resulting in insufficient whiteness of quartz sand and difficult to remove impurities.
The high-efficiency high-temperature acid leaching treatment process is adopted, including the steps of pre-acid leaching, first acid leaching treatment, water quenching, and second acid leaching treatment. The fluorine-containing waste sulfuric acid and reducing agent or chelating agent are used to significantly improve the cleaning effect of quartz sand through the permeation and reaction of the acid solution under high temperature conditions.
It achieves high purity and high whiteness of quartz sand, significantly improves the pickling efficiency, shortens the treatment time, and effectively absorbs fluorine-containing waste sulfuric acid, avoiding environmental pollution.
Smart Images

Figure BDA0005221396930000091 
Figure BDA0005221396930000092 
Figure BDA0005221396930000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz sand purification, and in particular to a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand. Background Art
[0002] Fluorine-containing waste sulfuric acid, due to its strong acidity and corrosiveness, will seriously corrode the treatment equipment. In addition, the effective separation technology of fluoride ions from other useful components in waste sulfuric acid is difficult, making harmless treatment and resource utilization a major problem. At present, the treatment of this type of fluorine-containing waste sulfuric acid often requires the comprehensive application of multiple processes, but the coordination and integration between the processes are highly complex, making it difficult to achieve the ideal treatment effect. Therefore, it is particularly urgent to explore efficient and economical solutions for the treatment of fluorine-containing waste sulfuric acid.
[0003] At present, quartz sand is widely used in the construction field, especially in the preparation of high-end building decoration materials. High-whiteness quartz sand can significantly enhance the aesthetic value and texture of the product. However, crude quartz sand often contains impurities such as iron and has insufficient whiteness, which has an adverse effect on the overall visual effect of building materials. In addition, if the pickling or impurity removal steps in the processing process are not performed properly, it is very easy to further reduce the whiteness of the quartz sand, and even cause obvious color difference. In view of this, it is particularly important to carry out refining treatment of crude quartz sand.
[0004] In the field of quartz sand refining, pickling process is an important means to improve product quality. Quartz sand refining pickling process mainly includes: single pickling agent pickling process (hydrochloric acid, sulfuric acid or hydrofluoric acid, etc.), mixed pickling agent pickling process (mixed hydrochloric acid and sulfuric acid, mixed hydrofluoric acid and oxalic acid), pickling combined with other processes (pickling-magnetic separation combined process, pickling-flotation combined process), etc. Traditionally, single pickling agent has been difficult to meet the increasingly stringent refining requirements due to its limited effect. Although mixed pickling agents can significantly improve the pickling effect, the high cost limits its widespread application. In addition, considering the strict restrictions on the discharge of chloride ion wastewater in environmental protection policies, many regions have banned the direct discharge of such wastewater, which undoubtedly further increases the difficulty of treatment. Summary of the invention
[0005] The purpose of the present invention is to provide a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, so as to solve the problem that fluorine-containing waste sulfuric acid cannot be processed in bulk and there are many limitations in the quartz sand pickling process.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, comprising the following steps:
[0008] (1) mixing a quartz sand raw material with a first acid solution and performing pre-acid leaching to obtain pretreated quartz sand;
[0009] (2) using a second acid solution to sequentially perform a first acid leaching treatment and a water quenching on the pretreated quartz sand to obtain a primary treated quartz sand;
[0010] (3) The first-treated quartz sand is subjected to a second acid leaching treatment using a third acid solution to obtain high-purity quartz sand.
[0011] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (1), the first acid solution comprises, by weight: 30 to 40 parts of fluorine-containing waste sulfuric acid, 0.5 to 2 parts of hydrogen peroxide, and 60 to 70 parts of water.
[0012] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (1), the solid-liquid ratio of the pre-acid leaching is 0.5 to 3:1, the temperature of the pre-acid leaching is 20 to 40°C, and the time of the pre-acid leaching is 3 to 6 hours.
[0013] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (2), the second acid solution comprises, by mass, 25 to 40 parts of fluorine-containing waste sulfuric acid, 1 to 5 parts of a reducing agent, and 60 to 70 parts of water.
[0014] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (2), the solid-liquid ratio of the first acid leaching treatment is 0.2 to 2:1, the temperature of the first acid leaching treatment is 80 to 100°C, and the time of the first acid leaching treatment is 1 to 3 hours.
[0015] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (2), the temperature of the water used for the water quenching is 1 to 10°C.
[0016] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (3), the third acid solution comprises, by mass, 30 to 40 parts of fluorine-containing waste sulfuric acid, 2 to 10 parts of a chelating agent, and 55 to 65 parts of water.
[0017] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, the reducing agent is thiourea dioxide;
[0018] The chelating agents include sodium citrate or sodium ascorbate.
[0019] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, in step (3), the solid-liquid ratio of the second acid leaching treatment is 0.2 to 2:1, the temperature of the second acid leaching treatment is 80 to 100°C, and the time of the second acid leaching treatment is 1 to 3 hours.
[0020] Preferably, in the high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, the fluorine-containing waste sulfuric acid in step (1) the first acid solution, step (2) the second acid solution and step (3) the third acid solution independently comprises the following components by mass fraction: HF: 2-6%, H 2 SO 4 :75~85%,H 2 O: 14~18%.
[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the process of the present invention, pre-acid leaching can initially reduce the impurity metal content of quartz sand, and help to improve the wettability of quartz sand in low-concentration hydrofluoric acid during the pickling process, open the quartz sand lattice system, and expand the quartz sand lattice cracks in the microscopic state, which is conducive to the further penetration of hydrofluoric acid liquid into the quartz lattice system in the subsequent two-step high-temperature acid leaching process, dissolving the internal impurities, improving the cleaning effect of high-temperature pickling quartz sand, and improving the efficiency of high-temperature pickling.
[0023] (2) The process of the present invention includes a two-step high-temperature acid leaching process, which can make the quartz sand fluffy, expand the lattice system, and further increase the cracks of the quartz sand; at the same time, under the conditions of high-temperature acid leaching, sulfuric acid changes from a low-energy state to a high-energy state, and can effectively penetrate into the pores and cracks of the quartz sand, and react violently with trace impurity elements such as Al, Ca, Cu, Fe, Mn, etc. contained in the quartz sand to generate soluble salts or complexes, wash and purify the quartz sand, and thus remove the impurity elements contained in the solid quartz sand inclusions. In addition, the two-step acid leaching process is set to high-temperature acid leaching (80-100°C), which is conducive to enhancing the molecular movement between the acid solution and the quartz sand, so that the acid solution can penetrate into the interior of the quartz sand particles faster, fully contact with the impurity elements and react. Compared with normal temperature acid leaching, the pickling efficiency of high-temperature acid leaching can be increased by more than 50%, greatly shortening the acid leaching treatment time. In addition, since the fluorine-containing waste sulfuric acid is diluted, the high-temperature acid leaching treatment at a low fluorine concentration can also maintain the integrity of the quartz sand crystals and avoid excessive corrosion or damage.
[0024] (3) Directly performing low-temperature water quenching after the first acid leaching treatment can not only further increase the microcracks generated in the quartz sand, provide favorable conditions for the subsequent second-step high-temperature acid leaching, and accelerate the treatment efficiency of the second-step high-temperature acid leaching; in addition, the physical scouring during the water quenching process also helps to remove residual impurities and reaction products attached to the surface of the quartz sand, thereby further improving the efficiency of the second-step high-temperature acid leaching treatment.
[0025] (4) Thiourea dioxide is added to the first step of high-temperature acid leaching. As a reducing agent instead of sodium dithionite, it can cooperate with the acidic components in the acid solution to improve the impurity removal effect. In an acidic environment, thiourea dioxide can release reducing sulfide ions or sulfite ions, which undergo redox reactions with iron ions, reducing them to a more soluble or easier to remove form. In the second step of high-temperature acid leaching, a chelating agent is added. The chelating agent can form a stable complex with metal ions, especially selectively bind to iron ions to form a difficultly soluble or insoluble complex precipitate, further improving the iron removal efficiency of quartz sand and improving the whiteness and purity of quartz sand.
[0026] (5) The present invention uses industrially difficult-to-treat fluorine-containing waste sulfuric acid as pickling liquid, combined with a high-temperature pickling process, which can not only effectively react with impurities in quartz sand to ensure that quartz sand crystals are not damaged, and achieve bulk consumption of fluorine-containing waste sulfuric acid, but also greatly shorten the time of acid leaching treatment, which is beneficial to cost reduction and efficiency improvement in the quartz sand refining industry, while eliminating the generation of Cl-containing wastewater. The generated acid leaching wastewater is easier to handle, meets the requirements of environmental friendliness, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0027] The present invention provides a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, comprising the following steps:
[0028] (1) mixing a quartz sand raw material with a first acid solution and performing pre-acid leaching to obtain pretreated quartz sand;
[0029] (2) using a second acid solution to sequentially perform a first acid leaching treatment and a water quenching on the pretreated quartz sand to obtain a primary treated quartz sand;
[0030] (3) The first-treated quartz sand is subjected to a second acid leaching treatment using a third acid solution to obtain high-purity quartz sand.
[0031] In the present invention, in step (1), the mass fraction of fluorine-containing waste sulfuric acid in the first acid solution is preferably 30 to 40 parts, more preferably 32 to 38 parts, and more preferably 38 parts.
[0032] In the present invention, in step (1), the mass fraction of hydrogen peroxide in the first acid solution is preferably 0.5 to 2 parts, more preferably 1.5 to 2 parts, and more preferably 1.5 parts.
[0033] In the present invention, in step (1), the mass fraction of water in the first acid solution is preferably 60 to 70 parts, more preferably 60.5 to 66 parts, and more preferably 60.5 parts.
[0034] In the present invention, in step (1), the solid-liquid ratio of the pre-acid leaching is preferably 0.5-3:1, more preferably 1.5-3:1, and more preferably 2:1; the temperature of the pre-acid leaching is preferably 20-40°C, more preferably 25-30°C, and more preferably 25°C; the time of the pre-acid leaching is preferably 3-6h, more preferably 4-6h, and more preferably 5h.
[0035] In the present invention, during the pre-acid leaching process in step (1), the first acid solution is circulated by a circulation pump so that the first acid solution is in a flowing state.
[0036] In the present invention, in step (1), after the pre-acid leaching, preferably the following step is further performed: washing until the washing waste liquid becomes neutral.
[0037] In the present invention, in step (2), the mass fraction of fluorine-containing waste sulfuric acid in the second acid solution is preferably 25 to 40 parts, more preferably 30 to 40 parts, and more preferably 36 parts.
[0038] In the present invention, in step (2), the weight percentage of the reducing agent in the second acid solution is preferably 1 to 5 parts, more preferably 3 to 5 parts, and more preferably 4 parts.
[0039] In the present invention, in step (2), the mass fraction of water in the second acid solution is preferably 60 to 70 parts, more preferably 60 to 67 parts, and more preferably 60 parts.
[0040] In the present invention, the reducing agent is preferably thiourea dioxide.
[0041] In the present invention, in step (2), the solid-liquid ratio of the first acid leaching treatment is preferably 0.2 to 2:1, more preferably 1 to 2:1, and more preferably 2:1; the temperature of the first acid leaching treatment is preferably 80 to 100°C, more preferably 90 to 100°C, and more preferably 90°C; the time of the first acid leaching treatment is preferably 1 to 3 hours, more preferably 2 to 3 hours, and more preferably 3 hours.
[0042] In the present invention, during the first acid leaching treatment in step (2), the second acid solution is circulated by a circulation pump so that the second acid solution is in a flowing state.
[0043] In the present invention, in step (2), the temperature of the water used for the water quenching is preferably 1 to 10°C, more preferably 1 to 6°C, and even more preferably 2°C.
[0044] In the present invention, in step (2), water quenching is performed immediately after the first acid leaching treatment.
[0045] In the present invention, in step (3), the mass fraction of fluorine-containing waste sulfuric acid in the third acid solution is preferably 30 to 40 parts, more preferably 33 to 36 parts, and more preferably 36 parts.
[0046] In the present invention, in step (3), the weight percentage of the chelating agent in the third acid solution is preferably 2 to 10 parts, more preferably 4 to 10 parts, and more preferably 8 parts.
[0047] In the present invention, in step (3), the mass fraction of water in the third acid solution is preferably 55 to 65 parts, more preferably 56 to 60 parts, and more preferably 60 parts.
[0048] In the present invention, the chelating agent preferably includes sodium citrate or sodium ascorbate, and more preferably includes sodium citrate.
[0049] In the present invention, in step (3), the solid-liquid ratio of the second acid leaching treatment is preferably 0.2 to 2:1, more preferably 1 to 2:1, and more preferably 2:1; the temperature of the second acid leaching treatment is preferably 80 to 100°C, more preferably 90 to 100°C, and more preferably 90°C; the time of the second acid leaching treatment is preferably 1 to 3 hours, more preferably 2 to 3 hours, and more preferably 3 hours.
[0050] In the present invention, during the second acid leaching treatment in step (3), the third acid solution is circulated by a circulation pump so that the third acid solution is in a flowing state.
[0051] In the present invention, in step (3), after the second acid leaching treatment, the following steps are preferably performed: washing until the washing waste liquid is neutral, drying, and screening.
[0052] In the present invention, the drying temperature is preferably 20 to 50°C, more preferably 25 to 40°C, and even more preferably 35°C.
[0053] In the present invention, the screening process is not limited, and screening can be performed according to the required mesh size.
[0054] In the present invention, the mass fraction of HF in the fluorine-containing waste sulfuric acid in the first acid solution in step (1), the second acid solution in step (2) and the third acid solution in step (3) is independently preferably 2-6%, more preferably 4-6%, and more preferably 6%.
[0055] In the present invention, in the fluorine-containing waste sulfuric acid of the first acid solution in step (1), the second acid solution in step (2), and the third acid solution in step (3), H 2 SO 4 The mass fraction of each of the above is preferably 75 to 85%, more preferably 78 to 82%, and even more preferably 80%.
[0056] In the present invention, in the fluorine-containing waste sulfuric acid of the first acid solution in step (1), the second acid solution in step (2), and the third acid solution in step (3), H 2 The mass fraction of O is independently preferably 14 to 18%, more preferably 14 to 16%, and even more preferably 14%.
[0057] In the present invention, the preparation methods of the first acid solution in step (1), the second acid solution in step (2), and the third acid solution in step (3) are not limited, and they only need to be mixed evenly.
[0058] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Example 1
[0060] The fluorine-containing waste sulfuric acid used in Example 1 includes the following components by mass fraction: HF: 6%, H 2 SO 4 : 80%, H 2 O: 14%;
[0061] This embodiment provides a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, comprising the following steps:
[0062] (1) By weight, 38 parts of fluorine-containing waste sulfuric acid, 1.5 parts of hydrogen peroxide, and 60.5 parts of water are mixed evenly to prepare a first acid solution; quartz sand raw material (iron content 452 ppm) is immersed in the first acid solution with a solid-liquid ratio of 2:1, and the first acid solution is always kept in a flowing state by a circulating pump, immersed at 25° C. for 5 hours, and then washed to neutrality to obtain pretreated quartz sand;
[0063] (2) By weight, 36 parts of fluorine-containing waste sulfuric acid, 4 parts of thiourea dioxide, and 60 parts of water are mixed evenly to prepare a second acid solution; the pretreated quartz sand is immersed in the second acid solution at a solid-liquid ratio of 2:1, and the second acid solution is always kept in a flowing state by a circulating pump, and is immersed at 90° C. for 3 hours; and then immediately quenched with water at 2° C. to obtain a first-treated quartz sand;
[0064] (3) By weight, 36 parts of fluorine-containing waste sulfuric acid, 8 parts of sodium citrate, and 60 parts of water were mixed evenly to prepare a third acid solution; the once-treated quartz sand was immersed in the third acid solution at a solid-liquid ratio of 2:1, and the third acid solution was kept in a flowing state by a circulating pump, and was immersed at 90° C. for 3 hours; then, the third acid solution was washed to neutrality, dried at 35° C., and four specifications of high-purity quartz sand of >20 mesh, 20-40 mesh, 40-70 mesh, and 70-120 mesh were sieved.
[0065] Example 2
[0066] The fluorine-containing waste sulfuric acid used in Example 2 includes the following components by mass fraction: HF: 2%, H 2 SO 4 : 80%, H 2 O: 18%;
[0067] This embodiment provides a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, comprising the following steps:
[0068] (1) By weight, 32 parts of fluorine-containing waste sulfuric acid, 2 parts of hydrogen peroxide, and 66 parts of water are mixed evenly to prepare a first acid solution; a quartz sand raw material (iron content 452 ppm) is immersed in the first acid solution with a solid-liquid ratio of 1.5:1, and the first acid solution is always in a flowing state by using a circulating pump, and is immersed at 40° C. for 4 hours, and then washed to neutrality to obtain pretreated quartz sand;
[0069] (2) By weight, 30 parts of fluorine-containing waste sulfuric acid, 3 parts of thiourea dioxide, and 67 parts of water are mixed evenly to prepare a second acid solution; the pretreated quartz sand is immersed in the second acid solution at a solid-liquid ratio of 1:1, and the second acid solution is always kept in a flowing state by a circulating pump, and is immersed at 100° C. for 2 hours; and then immediately quenched with water at 10° C. to obtain a first-treated quartz sand;
[0070] (3) By weight, 40 parts of fluorine-containing waste sulfuric acid, 4 parts of sodium ascorbate, and 56 parts of water were mixed evenly to prepare a third acid solution; the once-treated quartz sand was immersed in the third acid solution at a solid-liquid ratio of 1:1, and the third acid solution was kept in a flowing state by a circulating pump, and was immersed at 100° C. for 2 hours; then, the sand was washed to neutrality, dried at 25° C., and four specifications of high-purity quartz sand of >20 mesh, 20-40 mesh, 40-70 mesh, and 70-120 mesh were sieved.
[0071] Example 3
[0072] The fluorine-containing waste sulfuric acid used in Example 3 includes the following components by mass fraction: HF: 4%, H 2 SO 4 : 80%, H 2O: 16%;
[0073] This embodiment provides a high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, comprising the following steps:
[0074] (1) 35 parts of fluorine-containing waste sulfuric acid, 0.5 parts of hydrogen peroxide, and 64.5 parts of water are mixed uniformly by weight to prepare a first acid solution; quartz sand raw material (iron content 452 ppm) is immersed in the first acid solution with a solid-liquid ratio of 3:1, and the first acid solution is always kept in a flowing state by a circulating pump, immersed at 30° C. for 6 hours, and then washed to neutrality to obtain pretreated quartz sand;
[0075] (2) By weight, 40 parts of fluorine-containing waste sulfuric acid, 1 part of thiourea dioxide, and 60 parts of water are mixed evenly to prepare a second acid solution; the pretreated quartz sand is immersed in the second acid solution at a solid-liquid ratio of 0.5:1, and the second acid solution is always kept in a flowing state by a circulating pump, and is immersed at 80° C. for 1.5 hours; and then immediately quenched with water at 6° C. to obtain a first-treated quartz sand;
[0076] (3) By weight, 33 parts of fluorine-containing waste sulfuric acid, 2 parts of sodium citrate, and 65 parts of water were mixed evenly to prepare a third acid solution; the once-treated quartz sand was immersed in the third acid solution at a solid-liquid ratio of 0.5:1, and the third acid solution was kept in a flowing state by a circulating pump, and was immersed at 80° C. for 1.5 hours; then, the third acid solution was washed to neutrality, dried at 40° C., and four specifications of high-purity quartz sand of >20 mesh, 20-40 mesh, 40-70 mesh, and 70-120 mesh were sieved.
[0077] Comparative Example 1
[0078] This comparative example provides a treatment process for refining quartz sand. The difference from Example 1 is that the immersion temperature in step (2) is changed to 25°C and the immersion time is changed to 6 hours; the immersion temperature in step (3) is changed to 25°C and the immersion time is 6 hours. The other parameter conditions are the same as those in Example 1.
[0079] Comparative Example 2
[0080] This comparative example provides a treatment process for refining quartz sand, which differs from Example 1 in that water in the first acid solution, the second acid solution and the third acid solution is deleted, and other parameter conditions are the same as those in Example 1.
[0081] Comparative Example 3
[0082] This comparative example provides a treatment process for refining quartz sand, which differs from Example 1 in that step (1) is deleted, and other parameter conditions are the same as those in Example 1.
[0083] Comparative Example 4
[0084] This comparative example provides a treatment process for refining quartz sand, which differs from Example 1 in that the second acid solution in step (2) is replaced by water, and other parameter conditions are the same as those in Example 1.
[0085] Comparative Example 5
[0086] This comparative example provides a treatment process for refining quartz sand, which differs from Example 1 in that the water quenching in step (2) is deleted, and other parameter conditions are the same as those in Example 1.
[0087] Comparative Example 6
[0088] This comparative example provides a treatment process for refining quartz sand, which differs from Example 1 in that thiourea dioxide in the second acid solution is deleted, and the chelating agent in the third acid solution is deleted, and other parameter conditions are the same as those in Example 1.
[0089] The acid leaching treatment time of Examples 1 to 3 and Comparative Example 1 was compared, and the results are shown in Table 1.
[0090] Table 1. Comparison of two-step acid leaching treatment time of Examples 1 to 3 and Comparative Example 1
[0091]
[0092] The refined quartz sand products obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were tested, and the test results are shown in Table 2.
[0093] Table 2. Test results of quartz sand products obtained in Examples 1 to 3 and Comparative Examples 1 to 6
[0094]
[0095]
[0096] It can be seen from the test results of Examples 1 to 3 and Comparative Example 1 that, compared with the high-temperature acid leaching in the examples, Comparative Example 1 uses room-temperature acid leaching to purify quartz sand. The purity, whiteness and iron content of the quartz sand product are at the same level, and the treatment time required for the high-temperature acid leaching in the examples is greatly shortened, and the treatment efficiency is significantly improved. This shows that the high-temperature acid leaching process of the present invention has good treatment effect and shorter treatment time, is more suitable for large-scale industrial production, and is conducive to achieving cost reduction and efficiency improvement in the quartz sand pickling industry.
[0097] It can be seen from the test results of Example 1 and Comparative Example 2 that Comparative Example 2 uses undiluted fluorine-containing waste sulfuric acid to refine quartz sand. Although the differences in whiteness and iron content are not large, hydrofluoric acid easily reacts with quartz sand at a higher concentration to form fluorosilicates, which corrodes the lattice of quartz sand and causes the "collapse" of quartz sand cracks in a microscopic state, which is not conducive to the subsequent two-step high-temperature acid leaching treatment, resulting in a decrease in the purity of the quartz sand after pickling.
[0098] It can be seen from the test results of Example 1 and Comparative Example 3 that the whiteness of the product of Comparative Example 3 without pre-acid leaching is significantly reduced, and the iron content is also significantly increased. This shows that the scheme without pre-acid leaching cannot open the lattice system of quartz sand at the initial stage of treatment, and cannot make the subsequent two-step high-temperature acid leaching process further immerse into the interior of the quartz lattice system for impurity removal, and the final purity of quartz sand is also reduced.
[0099] It can be seen from the test results of Example 1 and Comparative Example 4 that in Comparative Example 4, the acid solution in the first step of acid leaching treatment is replaced with water, which reduces the iron removal effect and the whiteness value also decreases accordingly.
[0100] The test results of Example 1 and Comparative Example 5 show that the water quenching process in step (2) is omitted in Comparative Example 5, and both the iron removal effect and the whiteness value are reduced, indicating that the water quenching process helps to improve the effect of the second step of high-temperature acid leaching treatment.
[0101] It can be seen from the test results of Example 1 and Comparative Example 6 that the reducing agent and the chelating agent are omitted in Comparative Example 6, and the iron removal effect and the whiteness value are reduced, indicating that the aforementioned additives can assist the acid solution in an acidic environment to improve the impurity removal effect (especially iron removal).
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand, characterized in that: The following steps are involved: (1) mixing a quartz sand raw material with a first acid solution and performing pre-acid leaching to obtain pretreated quartz sand; (2) using a second acid solution to sequentially perform a first acid leaching treatment and a water quenching on the pretreated quartz sand to obtain a primary treated quartz sand; (3) The first-treated quartz sand is subjected to a second acid leaching treatment using a third acid solution to obtain high-purity quartz sand.
2. The high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1, characterized in that: In step (1), the first acid solution comprises, by weight, 30 to 40 parts of fluorine-containing waste sulfuric acid, 0.5 to 2 parts of hydrogen peroxide, and 60 to 70 parts of water.
3. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1 or 2, characterized in that: In step (1), the solid-liquid ratio of the pre-acid leaching is 0.5 to 3:1, the temperature of the pre-acid leaching is 20 to 40° C., and the time of the pre-acid leaching is 3 to 6 hours.
4. The high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1, characterized in that: In step (2), the second acid solution comprises, by weight, 25 to 40 parts of fluorine-containing waste sulfuric acid, 1 to 5 parts of a reducing agent, and 60 to 70 parts of water.
5. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1 or 4, characterized in that: In step (2), the solid-liquid ratio of the first acid leaching treatment is 0.2 to 2:1, the temperature of the first acid leaching treatment is 80 to 100° C., and the time of the first acid leaching treatment is 1 to 3 hours.
6. The high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 5, characterized in that: In step (2), the temperature of the water used for the water quenching is 1 to 10°C.
7. The high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1, characterized in that: In step (3), the third acid solution comprises, by weight, 30 to 40 parts of fluorine-containing waste sulfuric acid, 2 to 10 parts of a chelating agent, and 55 to 65 parts of water.
8. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 4 or 7, characterized in that: The reducing agent is thiourea dioxide; The chelating agents include sodium citrate or sodium ascorbate.
9. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 8, characterized in that: In step (3), the solid-liquid ratio of the second acid leaching treatment is 0.2 to 2:1, the temperature of the second acid leaching treatment is 80 to 100° C., and the time of the second acid leaching treatment is 1 to 3 hours.
10. A high-efficiency high-temperature acid leaching process for refining high-purity quartz sand according to claim 1 or 2, characterized in that: The fluorine-containing waste sulfuric acid in the first acid solution of step (1), the second acid solution of step (2) and the third acid solution of step (3) independently comprises the following components in mass fractions: HF: 2-6%, H2SO4: 75-85%, H2O: 14-18%.
Citation Information
Patent Citations
PRODUCTION OF QUARTZ-FREE INVESTMENT MATERIAL AND APPLICATION
ATE339929T1
Purification method for quartz sand
CN106082238A
Pickling purification method for quartz sand
CN116199228A
Chemical deironing and whitening process for quartz sand
CN118458785A
Quartz sand efficient pickling method capable of reducing acid medium consumption
CN118619285A
Cited By
Quartz sand purification method
CN121342038A